Perceptions of Regulatory Decision-Making for New Drugs From the Viewpoints of the Manufacturers in South Korea - Son, Kyung-Bok; Park, Sylvia (Frontiers in Medicine, 2022)
Regulatory decisions for new drugs approval present high uncertainty, low reversibility, the avoidance of observable errors, and high political stakes. However, research on the behavior of regulatory agencies is scarce, particularly in the context of more open decision-making processes. We aimed to evaluate the perceptions of regulatory decision-making for new drugs approval from the viewpoints of the manufacturers in South Korea. In 2019, employees in domestic (n = 5) and foreign (n = 7) manufacturers with expertise in regulatory affairs were invited to participate in a questionnaire survey and semi-structured group interview. We asked about the relevance of various criteria in regulatory decision-making, the participation of various stakeholders, and the degree of consent for new drug approval with uncertainty. The domestic and foreign manufacturers perceived that a regulatory decision made by the MFDS was solely based on technical merit within a closed decision-making system. They responded that safety, efficacy, and benefit-to-harm ratio were the most relevant criteria and the most prioritized criteria in regulatory decision-making. They also perceived that the MFDS was the sole relevant member in a regulatory decision. However, the foreign manufacturers disagreed that the regulatory agency and the advisory committee were independent of conflicts of interest, which might imply that regulatory decisions were occasionally determined by the agency given the political benefits and/or costs within a more open system. The role of an advisory committee in terms of deliberation and participatory democracy were requested to make politically legitimate regulatory decisions from the viewpoints of the manufacturers. However, their perceptions toward public involvement in regulatory decision-making is still at the early stage.